(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article discusses modern digital technologies used at the stage of pre-trial investigation in order to increase the effectiveness of prosecutorial supervision. The possibilities of automating accounting and information exchange, the introduction of audio and video recording of investigative actions, as well as the use of analytical platforms and systems of interdepartmental interaction are analyzed. It is shown that digitalization makes it possible to speed up the verification of legality, ensure transparency of processes and minimize procedural errors. Special attention is paid to the experience of the CIS countries, primarily Kazakhstan and Kyrgyzstan: specific electronic systems are considered, the use of electronic digital signatures and portals of the «Public Sector» for access of participants in the process to case files is described. International experience is also taken into account and recommendations are offered on the integration of technology into the activities of the prosecutor’s office. The findings highlight the need for further implementation of digital tools and coordination of the legislative framework to improve prosecutorial oversight.